Spatial Variability of Mechanical Properties of Sedimentary Rocks in the Jiu Valley Basin: A Stress-strain Curve Analysis - Mihaela Toderas (Research Advances in Environment, Geography and Earth Science Vol. 10, 2024)
The study aimed to evaluate the geomechanical characteristics of sedimentary rocks in the Jiu Valley coal basin, with the purpose of providing relevant data for the design and execution of mining works under safe conditions. A significant number of rock samples were analyzed, representative of the various lithological types and zones of the basin. Laboratory tests were conducted to determine the mechanical behavior of rocks under load, with a focus on strength, deformability, and failure mode. The results obtained highlighted a significant heterogeneity of geomechanical properties, influenced by factors such as mineralogical composition, geological structure, and degree of alteration. The study identified that the sedimentary rocks in Jiu Valley can be classified according to strength into three main categories: very low-strength rocks, low-strength rocks, and medium-strength rocks. A close correlation was also observed between the mechanical behavior of rocks and the presence of structural defects, such as fissures and fractures. A detailed analysis of stress-strain curves allowed the identification of two main types of behavior: elastic, with work hardening, and inelastic, characteristic of low-strength rocks. These differences in behavior have important implications for the stability of mining works, influencing the mode of crack propagation and deformations induced by mining. In conclusion, the study highlighted the geomechanical complexity of sedimentary rocks in the Jiu Valley basin. The obtained data can be used to develop more accurate numerical models and to optimize the design of mining works, thus contributing to increasing the safety and efficiency of mining operations in this area. Through extensive laboratory and field investigations, coupled with analytical studies, we have obtained objective data on the geomechanical laws governing the rock mass. These findings allow for a quantitative and qualitative description of its deformation behavior, aiding in the understanding of stress conditions and facilitating the development of new methods to ensure the stability of mining operations. These studies focused on determining the characteristics of strength and deformation necessary to classify these rocks and facilitate the study of their rheological behavior.